Associations of Walking Activity With Hypertensive Mediated Organ Damage in Community-Dwelling Elderly Chinese: The Northern Shanghai Study - Lyu, Yuyan; Yu, Shikai; Chi, Chen; Teliewubai, Jiadela; Li, Jue; Blacher, Jacques; Pu, Jun; Zhang, Yi; Xu, Yawei (Frontiers in Cardiovascular Medicine, 2021)
Background: Walking, as the most common campaign in older people, is recommended to improve their cardiovascular health. However, the direct association between weekly walking activity and asymptomatic hypertensive mediated organ damage (HMOD) remains unclear. Methods: 2,830 community-dwelling elderly subjects (over 65 years) in northern Shanghai were recruited from 2014 to 2018. Weekly walking activity was assessed by International Physical Activity Questionnaires (IPAQ). Within the framework of comprehensive cardiovascular examinations, HMOD, including left ventricular mass index, peak transmitral pulsed Doppler velocity/early diastolic tissue Doppler velocity, creatinine clearance rate, urinary albumin–creatinine ratio, carotid-femoral pulse wave velocity (cf-PWV), carotid intima–media thickness (CIMT), arterial plaque, and ankle-brachial index (ABI), were all evaluated. Results: 1,862 (65.8%) participants with weekly walking activity showed lower CIMT, lower cf-PWV, fewer abnormal ABI, and lower prevalence of hypertension and coronary heart disease (p < 0.05). Walking activity was negatively correlated with age and smokers (correlation coefficient: −0.066, −0.042; both p < 0.05). After adjusting for cardiovascular risk factors and concomitant diseases, walking activity was significantly associated with better indicator of most vascular HMOD in multivariate logistic regressions, including arterial stiffness [odds ratio (OR) = 0.75, p = 0.01], increased CIMT (OR = 0.70, p = 0.03), and peripheral artery disease (OR = 0.72, p = 0.005), but not cardiac or renal HMOD. Subgroup analysis further showed that walking duration ≥1 h/day was significantly associated with decreased risk of most vascular HMOD after adjustment for confounders and moderate-to-vigorous physical activity based on IPAQ (all p < 0.05). Conclusions: In the community-dwelling elderly Chinese, there was a significant negative association of weekly walking activity with vascular HMOD, but not cardiac or renal HMOD. Increased daily walking duration, but not walking frequency, was significantly associated with improved vascular HMOD. Hence, increasing daily walking duration seems to encourage a healthy lifestyle in terms of vascular protection. Clinical Trial Registration:ClinicalTrials.gov, identifier: NCT02368938.